2020
DOI: 10.26434/chemrxiv.12058437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanocrystals of Lead Chalcohalides: A Series of Kinetically Trapped Metastable Nanostructures

Abstract: We report the colloidal synthesis of a series of surfactant-stabilized lead chalcohalide nanocrystals. Our work is mainly focused on Pb<sub>4</sub>S<sub>3</sub>Br<sub>2</sub>, a chalco-halide phase unknown to date that does not belong to the ambient-pressure PbS – PbBr<sub>2</sub> phase diagram. The Pb<sub>4</sub>S<sub>3</sub>Br<sub>2</sub> nanocrystals herein feature a remarkably narrow size distribution (with a size dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This is demonstrated on assemblies of recently synthesized ultrathin PbS orthorhombic nanoplatelets (Figure 6a-d) 35 and spheroidal rock-salt PbS nanocrystals (Figure 6e-g). 36 For both the morphologies, particles assemble with the same crystal planes parallel to the substrate [cubic (200) = orthorhombic (400)], a circumstance convenient for the comparison. Table 1 summarizes the result of the fits.…”
Section: Resultsmentioning
confidence: 99%
“…This is demonstrated on assemblies of recently synthesized ultrathin PbS orthorhombic nanoplatelets (Figure 6a-d) 35 and spheroidal rock-salt PbS nanocrystals (Figure 6e-g). 36 For both the morphologies, particles assemble with the same crystal planes parallel to the substrate [cubic (200) = orthorhombic (400)], a circumstance convenient for the comparison. Table 1 summarizes the result of the fits.…”
Section: Resultsmentioning
confidence: 99%
“…PbS nanocrystals were grown via a modification of the method we originally published for the synthesis of lead chalcohalide nanocrystals. 36 Briefly, 111 mg (0.4 mmol) of PbCl2 were dissolved in a 20 mL flask containing 10 mL ODE, 750 μL OLAM and 750 μL OA at 120°C under continuous stirring. The solubilization of PbCl2 is slow and might be incomplete.…”
Section: Methodsmentioning
confidence: 99%
“…30,31 Our group pioneered the investigation of lead chalcohalides at the nanoscale, discovering two additional compounds (Pb4S3Br2 and a yet not identified Pb-S-Cl phase) in the form of NCs. 25 More recently, we found that Pb4S3Br2 can match epitaxially the CsPbX3 perovskite to form colloidal heterostructures, thus demonstrating a remarkable synthetic and structural compatibility. 26 Here we focus our attention on the lead sulfochlorides, demonstrating that the yet unknown Pb-S-Cl phase obtained through direct synthesis is Pb3S2Cl2, whose structure, here identified as monoclinic and solved for the first time, is a distorted version of the cubic Pb3Se2Br2 prototype (Figure 1, left panels).…”
Section: Introductionmentioning
confidence: 95%
“…6,7,12,13,19 There, the combination of as little as four elements (Cs, Pb, X and E, where X = F, Cl, Br or I and E = S, Se or Te) can yield NCs of a variety of phases: the binaries CsX, PbX2 and PbE, 6,7,[20][21][22] the well-known cesium lead halides (Cs4PbX6, CsPbX3, and CsPb2X5), 12,19,23,24 and the still little explored lead chalcohalides (Pb4S3Br2 and Pb4S3I2). 25,26 All these compounds are often obtained under similar reaction conditions, and can therefore compete during the synthesis, requiring a careful tuning of the synthetic protocols to achieve the impurity-free synthesis of the desired product. This condition is not dissimilar from that of many organic chemistry reactions, where two molecules can react following different pathways and resulting in different products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation